Deep Brain Stimulation in Parkinson's Disease: New and Emerging Targets for Refractory Motor and Nonmotor Symptoms. (6th July 2017) - Anderson, Dustin; Beecher, Grayson; Ba, Fang
Abstract : Parkinson's disease (PD) is a progressive neurodegenerative condition characterized by bradykinesia, tremor, rigidity, and postural instability (PI), in addition to numerous nonmotor manifestations. Many pharmacological therapies now exist to successfully treat PD motor symptoms; however, as the disease progresses, it often becomes challenging to treat with medications alone. Deep brain stimulation (DBS) has become a crucial player in PD treatment, particularly for patients who have disabling motor complications from medical treatment. Well-established DBS targets include the subthalamic nucleus (STN), the globus pallidus pars interna (GPi), and to a lesser degree the ventral intermediate nucleus (VIM) of the thalamus. Studies of alternative DBS targets for PD are ongoing, the majority of which have shown some clinical benefit; however, more carefully designed and controlled studies are needed. In the present review, we discuss the role of these new and emerging DBS targets in treating refractory axial motor symptoms and other motor and nonmotor symptoms (NMS).